New Asia style contemporary tropical living in Singapore - Marsden, Jane Doughty (Singapore Periplus, 2002)
"More than ever before, interior design is a global affair. And more than ever, Westerners are eager to try out elements of Asian design and architecture. This book is the ultimate resource for professional and amateur designers seeking to recreate the mysterious elegance, balance, and beauty of Asian design. Through the magic of Masano Kawana's beautiful full-color photography, New Asian Style explores more than 30 stunning contemporary houses and homes from Singapore, all of which stand as examples of interior decorating and style that transcend their Eastern origins"--Provided by publisher.
Keywords: Interior decoration -- Asian Influence; Interior decoration -- Singapore -- History -- 20th Century